DISINFORMATION AND DIGITAL ELECTORAL CRIMES: CHALLENGES FOR DEMOCRACY (CIPEEX, 2025)
Contemporary politics faces profound transformations driven by technological advances,which generate both positive and negative effects. Among the main challenges are the spread ofdisinformation and the rise of digital electoral crimes, which threaten democratic integrity.This paper aims to examine the effects of disinformation and digital electoralcrimes on democracy, focusing on the application of technologies such as artificial intelligence in politicalcampaigns. This study was developed based on a methodological approach of bibliographical researchand a review of Brazilian regulations, such as Law No. 9,504/1997 and TSE resolutions. The dataobtained demonstrate that the application of technologies, such as artificial intelligence, in political campaignshas the potential to influence voters in a manipulative manner, requiring effective measures to combatfake news, especially in the Brazilian electoral context. For this to happen, it is necessary tostrengthen political education, contributing to the formation of a critical andconscious society, capable of resisting misinformation and illicit practices. In this context, the responsible use oftechnology, combined with the dissemination of truthful information and the appreciation of ethics in politics, canstrengthen democracy. Therefore, although the challenges are great, it is possible to move toward amore reliable and representative electoral system. A well-informed society is the foundation of asolid democracy, capable of protecting itself against abuse and manipulation, reaffirming the importance ofeducation, ethics, and oversight in the current political landscape.
Keywords: Justiça; Eleitoral; Eleições; Democracia; Transparência; Fiscalização